Applying moving bed biofilm reactor for removing linear alkylbenzene sulfonate using synthetic media - Jalaleddin Mollaei; Seyed Bagher Mortazavi; Ahmad Jonidi Jafari (Iranian Journal of Health, Safety and Environment, 2015)
Detergents and problems of their attendance into water and wastewater cause varied difficulties such as producing foam, abnormality in the growth of algae, accumulation and dispersion in aqueous environments. One of the reactors was designated with 30% of the media with the similar conditions exactly same as the other which had filling rate about 10 %, in order to compare both of them together. A standard method methylene blue active substance was used to measure anionic surfactant. The concentrations of linear alkylbenzene sulfonate which examined were 50, 100, 200, 300 and 400 mg/l in HRT 72, 24 and 8 hrs. The removal percentage for both of reactors at the beginning of operating at50 mg/l concentration of pollutant had a bit difference and with gradually increasing the pollutant concentration and decreasing Hydraulic retention time, the variation between the removal percentage of both reactors became significant as the reactor that had the filling rate about 30 %, showed better condition than the other reactor with 10 % filling rate. Ideal condition in this experiment was caught at hydraulic retention time about 72 hrs and 200 mg/l pollutants concentration with 99.2% removal by the reactor with 30% filling rate. While the ideal condition for the reactor with 10% filling rate with the same hydraulic retention time and 100 mg/l pollutants concentrations was obtained about 99.4% removal. Regarding anionic surfactant standard in Iran which is 1.5 mg/l for surface water discharge, using this process is suitable for treating municipal wastewater and industrial wastewater which has a range of the pollutant between 100-200 mg/l. but for the industries that produce detergents products which make wastewater containing more than 200 mg/l surfactants, using secondary treatment process for achieving discharge standard is required.